Rebaban Performance in The Song “Gorompol” at Kliningan Sunda - Tresnadi, Soni; Maulana, Marsel Ridky; Suparli, Lili; Irawan, Endah (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2025)
The study discusses the use of rebaban in “Gorompol” sekar-gending in Sundanese Kliningan performances. The study focuses on the role of the Sundanese rebab instrument in accompanying and enriching the musical composition, as well as how the rebaban playing pattern shapes the ornamentation in the “Gorompol” sekar-gending. The research method used is content analysis with data collection techniques through observation, interviews with art practitioners, and analysis of performance recordings. The results show that the Sundanese rebab plays a central role in the “Gorompol” sekar-gending, providing expressive nuances through accompanying melodies (pamurba lagu) and dynamic interactions with gamelan instruments. The Sundanese rebab playing technique in the “Gorompol” sekar-gending emphasizes embellishments (reureueus) and ornamentation variations that harmonize with the vocals and rhythm of the Sundanese gamelan. The skill of Sundanese rebab players in interpreting dynamics and ornamentation is an important factor in presenting the distinctive atmosphere of Sundanese Kliningan performances. Thus, this study deepens the understanding of the role of the Sundanese rebab in the “Gorompol” sekar-gending, and can also be a reference for the development of Sundanese rebab instrument learning methods and the preservation of Sundanese gamelan aesthetics in the context of Sundanese traditional music performances.